2012
DOI: 10.5812/jjm.4756
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Drug Sensitivity and Bacterial Prevalence of UTI in Tribal Population of Paschim Medinipur, West Bengal, India

Abstract: The result will be very much helpful for medical practitioners and clinicians of the region to create a common database for UTI causing microorganisms and their antibiogram profile. Background:There is paucity of information in regards to prevalence of bacteria in urinary tract infection (UTI) in tribal population. Objectives: This study was conducted to observe dominant organisms causing UTI in tribal community of Medinipur, West Bengal, India and evaluate their sensitivity to common antibiotics. Patients and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The other isolate which was identified in this study was Pseudomonas aeruginosa with a proportion of (12.6%), this result was close to studies conducted in Metu, Ethiopia (10.35) 45 and Harar, Ethiopia (10%). 37 But it was higher than different studies in India (4.53%), 46 Nigeria (4.4%), 43 Harar Ethiopia (6.4%), 42 Harar, Ethiopia (3.1%), 24 Addis Ababa, Ethiopia (1.2%) 33 and Hawassa, Ethiopia (3.0%). 47 In this study the proportion of CoNS was (11.8%) this result is closer to two studies previously conducted in Harar, Ethiopia (7.9%) and (8.2%), 24,42 this result is higher than a study conducted in India (2.7%).…”
Section: Discussionmentioning
confidence: 78%
“…The other isolate which was identified in this study was Pseudomonas aeruginosa with a proportion of (12.6%), this result was close to studies conducted in Metu, Ethiopia (10.35) 45 and Harar, Ethiopia (10%). 37 But it was higher than different studies in India (4.53%), 46 Nigeria (4.4%), 43 Harar Ethiopia (6.4%), 42 Harar, Ethiopia (3.1%), 24 Addis Ababa, Ethiopia (1.2%) 33 and Hawassa, Ethiopia (3.0%). 47 In this study the proportion of CoNS was (11.8%) this result is closer to two studies previously conducted in Harar, Ethiopia (7.9%) and (8.2%), 24,42 this result is higher than a study conducted in India (2.7%).…”
Section: Discussionmentioning
confidence: 78%
“…Comparable findings have been described by Zorc et al ( 17 ), Bitsori et al ( 5 ), and Nickavar and Sotoudeh ( 15 ). Several investigations that were conducted on UTIs caused by P. aeruginosa in India ( 16 ), Iran ( 18 , 19 ), Kolkata ( 20 ), and Nigeria ( 21 ) revealed that the total prevalence of bacteria is about 3 - 16% which was considerable. Differences in the type of UTIs, method of sampling, number of samples collected, method of experiment, sex and age of patients, and the geographical area where the samples were collected are the main contributing factors for the differences in the prevalence of P. aeruginosa in various investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis of UTI is defined on the basis of significant colony count of ≥10 5  cfu/ml for Gram-negative and Gram-positive bacteria [7]. Growths on the culture media were identified by using bacterial growth characteristics (morphology), Gram staining [19, 20] and general biochemical tests [21, 22]. …”
Section: Methodsmentioning
confidence: 99%